Promising tomato hybrids for summer-autumn turnover in protected ground in Dagestan - P. M. Akhmedova (Овощи России, 2021)
Relevance. The region continues to build new industrial greenhouses every year, as well as mass construction of winter film greenhouses in the farms of the population of Flat and foothill Dagestan. Today, there are more than 250 hectares of them.Methods. Experimental work was carried out in the greenhouse of LLC Agro-AS in 2019-2020. Carried out selection and evaluation of promising hybrids of tomato for the summer-autumn turnover in greenhouses. Studied the duration of interphase periods, estimated the percentage of fruit set in the inflorescence, determined the yield of tomato hybrids, and calculated the most economically promising ones for the natural and climatic conditions of Dagestan.Results. For the first time in the conditions of flat Dagestan, the following experimental data are proved the main elements of industrial technology for obtaining a high yield of tomatoes in protected ground structures using low-volume hydroponic technology on a coconut substrate were experimentally justified; highly productive tomato hybrids were identified for various protected ground structures; F1 hybrids were distinguished by good yield from the second decade of September to the second decade of December; hybrids such as Men-Shuai F1 and Mamston F1 provided 24.3 kg/m2 and 23.1 kg/m2 , respectively, according to the highest percentage of fruit setting, as well as the total and commercial yield. The term of planting seedlings in the substrate in the summer and autumn turnover in the conditions of the suburbs of Makhachkala on July 10 is economically effective, which ensures a high yield and net income per unit area. At the selling price of tomato fruits of 100-110 rubles per 1 kg, the profitability of production, depending on the timing of harvesting and sales, was 100-122%.